BEHAVIORAL LAW AND ECONOMICS: MULTIDISCIPLINARITY IN ACTION - Mojašević, Aleksandar (Zbornik radova Pravnog fakulteta u Nišu, 2020)
This paper presents the theoretical foundations of Behavioral Law and Economics (BLE), as well as the practical implications of some key findings of this discipline. The author examines the roots of this discipline, its development, its most important representatives and opponents, and, most importantly, the boundaries of this discipline in relation to the neoclassical Law and Economics (L&E), on the one hand, and Behavioral Economics, on the other hand. Since BLE “borrows” certain findings from psychology (especially from social psychology), it raises the issue of interconnection between these two disciplines, which will be analyzed en passant. The central questions that need to be addressed are whether BLE is a special and sufficiently developed scientific discipline, or is it only a theoretical upgrade over its base (the neoclassical L&E), and what are the practical achievements and significance of its key findings in the field of dispute resolution policy?